PEMANFAATAN KECAMBAH TAUGE UNTUK MENGATASI KERONTOKAN RAMBUT WANITA BERJILBAB - Amelia, Yola; Rostamailis, Rostamailis; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Hair loss is a common disander that accurs in human. If it happen continously will cause baldness. To overcome the hair loss we use Touge as a treatment. This study aim is to analyse the benefit of Touge to overcome the hair losss in hijab’s woman the reseach was assessed on the amount of hair loss by using a pull test and counting the hair loss during 24 hours. This a Quasi Experimental design and Non Equivalent control group design. The object of this reseach is women in hijab with hair loss and dry type. Samples are 6 female students who wear Hijab and experience hair loss more than 80 strands each day taken with purposive sampling technique and carried out volunteer. Data collection techniques through direct observation using observation sheet Data were analyzed using descriptive analysis, while hypothesis testing using independent sample t test. The results of research conducted in 9 times the treatment for 28 days showed that the control group (X0) does not show a significant change in the results while the experiment (X1) shows a significant change in the results. Calculation techniques pull test stating that t> t table (1,993> 1,860) and average calculation Hair Loss 1 x 24 hours after treatment revealed that the price t count> t table (4,484> 1,833) it is proved that the hypothesis there is no difference in the effect of the use of Touge against hair loss is not acceptable at 5% significance level.Kata kunci: Touge, Hair Loss